Effects of melatonin on uterine hypertrophy/hyperplasia: A preliminary experimental rat study - Mustafa Can Sivas; Omer Lutfi Tapisiz; Rasit Tan Ayik; Devrim Kahraman; Sadiman Kiykac Altinbas; Ozlem Moraloglu Tekin (Heliyon, 2020)
Endometrial hyperplasia is a process of endometrial proliferation that results in a thickening of the endometrial tissue. Melatonin might be able to change the pathophysiological process and prognosis into a positive way that might prevent and heal endometrial hyperplasia, which is the first stage of endometrial cancer.For this perspective, we tried to investigate the effect of melatonin on uterine hypertrophy/hyperplasia in an experimental rat model. Forty Wistar-Albino rats were undergone bilateral oophorectomy and randomized into four groups. To create a model of uterine hypertrophy/hyperplasia in all groups, except the control group [C] (n = 10), 4 mg/kg/day estradiol hemihydrate were given for 14 days. The uterine hypertrophy/hyperplasia was evaluated histopathologically in the left uterine horns, then the groups were treated for 14 days as follows; melatonin (10 mg/kg/day/po) [M] (n = 10), melatonin + estradiol hemihydrate (10 mg/kg/day/po and 4 mg/kg/day/po) [M + E] (n = 10), and dark environment [D] (n = 10). Finally, the effects of the melatonin were examined histopathologically in the right uterine horns.An uterine hypertrophy/hyperplasia model was established in all groups compared to the control group (p < 0.05). In the [M] and [M + E] groups, epithelial cell height and luminal epithelial cell height significantly decreased (41μm vs 12μm, p = 0.005; 14μm vs 10μm, p = 0.005, respectively for [M] group) and (32μm vs 14μm, p = 0.012; 17μm vs 10μm, p = 0.017, respectively for [M + E] group). The [D] group exhibited a significant decrease in epithelial cell height (33μm vs 20μm, p = 0.017).With or without estrogen exposure, melatonin-treated and physiologically melatonin-released rats experienced a significant uterine hypertrophy/hyperplasia recovery. Melatonin may have protective effects on endometrial hyperplasia.